OP0192 Sirtuin Deacetylase 2 Inhibition Suppresses Inflammatory Activation of Rheumatoid Arthritis Fibroblast-Like Synoviocytes and IFN-Γ–Differentiated Macrophages. (10th June 2014) - Mohammadi, E.; Angiolilli, C.; Kabala, P.; Tak, P.P.; Baeten, D.; Husseini Shirazi, F.; Reedquist, K.
Abstract : Background: Rheumatoid arthritis (RA) is characterized by proliferation of synovial fibroblasts (FLS), activation of these cells by synovial macrophages (Mϕ), and production of pro-inflammatory proteins. As genetic backgrounds do not completely explain the etiology of RA, a growing attention has focused on potential epigenetic contributions to inflammation. Objectives: Here we examined the role of the closely related epigenetic regulatory proteins sirtuin 1 (Sirt1) and sirtuin 2 (Sirt2), class III histone deacetylases, in the inflammatory activation of RA FLS and human macrophages. Methods: Sirt1 and Sirt2 mRNA and protein expression was measured in RA FLS following stimulation with IL-1β and TNF-α. RA-FLS production of IL-6, IL-8, MMP-1 and MMP-3 mRNA and protein expression in response to IL-1β, in the absence or presence of specific inhibitors for Sirt1 and Sirt2, was measured by quantitative PCR (qPCR) and ELISA. The expression of 84 genes regulated by IL-1β in RA FLS were analyzed by qPCR array in the presence or absence of Sirt2-specific inhibitor. Monocytes obtained from healthy volunteers were differentiated into either M1 or M2 macrophages with human recombinant IFN-γ or IL-10 for 7 days. Macrophage production of IL-6 and IL-8 in response to LPS stimulation in the absence or presence of Sirt inhibitors was assessed by ELISA. Results: The expression of Sirt1 was enhanced following RA FLS IL-1β stimulation, while Sirt2 expression was significantly reduced (p<0.05). Pharmacological inhibition of Sirt2, but not Sirt1, significantly reduced RA FLS expression of IL-6, IL-8, and MMP-3 mRNA, in response to IL-1β stimulation (p<0.05), an effect mimicked at the protein level. qPCR array analysis demonstrated that mRNA expression of 18 of 84 genes induced by IL-1β in RA FLS (n=3) were significantly reduced by 50% or more in the presence of Sirt2 inhibitor. Furthermore Sirt2 inhibitor reduced LPS-induced levels of IL-8 in IFN-γ–but not IL-10–differentiated macrophages. Conclusions: Our studies identify Sirt2 as a novel epigenetic regulator of inflammatory activation of macrophages and RA FLS. Disclosure of Interest: E. Mohammadi: None declared, C. Angiolilli: None declared, P. Kabala: None declared, P. Tak Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, D. Baeten: None declared, F. Husseini Shirazi: None declared, K. Reedquist: None declared DOI: 10.1136/annrheumdis-2014-eular.4012